Unraveling the Determinants of Dengue Fever Incidence in Indonesia: A Systematic Review of Environmental and Behavioral Factors - Waskito, Agung; Sutriyawan, Agung; Romilian, Agung; Darmanto, Darmanto; Nugraheni, Sri Achadi (YCAB Publisher, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a significant public health issue in Indonesia, with an increasing incidence rate. Various factors, including environmental, social, and behavioral aspects, contribute to DHF. Objective: This systematic review aims to identify and analyze the factors influencing DHF incidence in Indonesia and provide recommendations for interventions that could reduce the incidence of this disease. Method: This review was conducted following PRISMA guidelines, which include a systematic search across five databases (Scopus, PubMed, Science Direct, Oxford Academic, and Emerald) for articles published between 2014 and 2023. Inclusion criteria included observational studies reporting quantitative relationships between determining factors and DHF incidence. After screening, 14 articles meeting the criteria were included in the analysis. Results: The review findings indicate that factors such as mosquito density, temperature, humidity, public knowledge about DHF, and mosquito breeding site elimination practices have a significant relationship with DHF incidence. In addition, socio-economic factors and endemic status also contribute to the increasing incidence. Conclusion: Enhancing public knowledge and prevention practices is essential in reducing DHF incidence. Community-involved education programs and further research are needed to develop effective interventions. Keywords: Dengue Hemorrhagic Fever; Determining Factors; Indonesia; Systematic Review, Mosquito Density